FT-IR Spectroscopic Study of the Radiation-Chemical Decomposition of n-Hexane on Nano-ZrO2 - Agayev, T.N.; Gadzhieva, N.N.; Melikova, S.Z.; Musayeva, Sh.Z.; Aliyev, A.G. (Physics and Chemistry of Solid State, 2023)
The radiation-chemical decomposition of n-hexane in the nano-ZrO2 +n-hexane system under the action of gamma radiation at room temperature is studied by the method of Fourier-IR spectroscopy. The molecular and dissociative form of adsorption of n-hexane in zirconium nanodioxide was revealed. The intermediate products of the radiation-heterogeneous decomposition of n-hexane were analyzed.